Organocatalyzed asymmetric [2+2] cycloaddition of saccharin-derived endocyclic ketimines and allenoates for the synthesis of fused azetidines - Xinyu Liu; Yunfeng Zhang; Luning Zhou; Dehai Li; De Wang (Tetrahedron Chem)
We report a novel enantioselective [2 + 2] cycloaddition of allenoate and endocyclic ketimine derived from saccharin, catalyzed by a chiral tertiary amine. The methodology enables the synthesis of fused tricyclic azetidines with a quaternary stereogenic center, exhibiting high enantioselectivity and efficiency. The broad range of substrates demonstrate the generality of the protocol, and the resulting functional products can be easily converted into a variety of valuable synthons such as thiazepine derivatives.